The Effect of Paid Vacation on Health: Evidence from Sweden - Thomas Hofmarcher (Lund University, School of Economics and Management, Department of Economics, 2018)
This study estimates the causal effect of paid vacation on health. Using register data on the universe of central government employees in Sweden, I exploit an age-based rule stipulated in the collective agreement covering these employees. I achieve identification by combining a regression discontinuity with a difference-in-differences design to control for time-invariant differences between consecutive birth cohorts and isolate the true effect at two separate discontinuities at ages 30 and 40. The main results indicate that an increase of three paid vacation days at age 30 and four days at age 40 do not cause significant changes in health, as proxied by visits to specialized outpatient care, inpatient admissions, and long-term sick leaves. These findings challenge the anecdotal view of additional paid vacation days as an adequate means to improve workers' health.
Keywords: I18; J22; J81; M52; 330; health; vacation; holiday; annual leave; working time